Enhanced anti-tumor effect of liposomal Fasudil on hepatocellular carcinoma in vitro and in vivo. - Ying Zhao; Yu Zhang; Milad Vazirinejad Mehdiabad; Ke Zhou; Yuyuan Chen; Lei Li; Jun Guo; Chuanrui Xu (PLoS ONE, 2019)
Hepatocellular carcinoma (HCC) is one of the most malignant cancers and the treatment options for this disease are limited and generally not effective. ROCK has been reported to be highly expressed in many cancer types and its inhibitor Fasudil has shown anti-cancer potential. However, its high toxicity and low solubility restrict its clinical application. Here, we report that Fasudil is effective against HCC and that a liposomal formulation (Lip-Fasudil) can enhance the anti-tumor effects of this drug both in vitro and in vivo. In vitro, Fasudil inhibited HCC cell growth with IC50 values of 0.025-0.04 μg/μL, with Lip-Fasudil showing slightly improved cytotoxicity with IC50 values of 0.02-0.025 μg/μL. Cellular mechanistic analysis indicated that Fasudil induced cell cycle arrest at the G2/M phase and that Lip-Fasudil enhanced this effect. Intriguingly, no apoptosis was detected in Fasudil- or Lip-Fasudil-treated HCC cells. In vivo, Fasudil inhibited the growth of HCC xenografts by 23% in nude mice. However, Lip-fasudil exerted anti-tumor effects (57% tumor inhibition) that were superior to those of Fasudil and similar to those of Topotecan (66%). In addition, Lip-fasudil resulted in an increased distribution of Fasudil in tumor tissues but a reduced distribution in normal organs. In conclusion, our results proved that Fasudil has the potential to be used for HCC treatment and that a liposomal formulation (Lip-Fasudil) could enhance anti-tumor efficacy and reduce systemic toxicity.